Syar’i Hijab Culture and Its Implications For Santriwati at Pondok Pesantren Putri Darusshoolah Pusat Pakong - Sa'diyah, Fatichatus; Anur, Homuud; Honda, Zein; Jie, Lie; Jixiong, Cai (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2021)
Hijab there are tools used to cover the head, basically this hijab is variegated in shape. There is such a thing as jilboob, khimar, hijab and niqab. This study focused on the syar’i headscarf used in the daily lives of Darussholah’s female students in pakong center. This research uses qualitative methods with a phenomenological approach. The cultural implications of the syar’i hijab show a positive thing for students, even in this pesantren applying this syar’i hijab in their daily lives. Basically, the obligation to wear this hijab has been mandated in the Qur’an and hadith, even it has been practiced by the wives of the Prophet Muhammad saw. The benefits that can be felt when a Muslim woman wears a hijab among them can make the woman avoid distractions, her muruah is awake, maintain chastity and avoid anathema of Allah swt